Development and quality evaluation of small rock oyster sauce from Saccostrea spp. - Jerson C. Sorio; Jedith C. Sorio; Josie Manoza; Andrei Gonzales; Ave Lalaguna (Journal of Fisheries, 2020)
Small rock oyster (Saccostrea spp.) are abundant in the Province of Samar and presently there is no oyster sauce produced from this species available in the Philippine markets. Hence, this study aimed to produce small rock oyster sauce at different concentrations (i.e. 70, 80 and 90%; treatments 1–3) and investigated their microbial and sensorial qualities. Based on the result of the overall acceptability of sensory evaluation, treatment 1 containing 70% of small rock oyster extract showed no significant difference with the control commercial oyster sauce suggesting that the treatment 1 is the most acceptable product. There is no microbiological standard limit for fermented fishery products in the Philippines. The total plate counts of the treatments ranged from 3.64 to 4.62 log CFU ml–1. Halophilic bacteria were present in all treatments, ranging from 3.49 – 4.67 log CFU ml–1. Also, lactic acid bacteria were detected in all treatments, ranged from 1.75 – 3.07 CFU ml–1. This study concludes that the small rock oyster sauce produced locally can compete with the available commercial oyster sauces in the market.